Pengaruh Active Stretching Otot Plantar Flexor Ankle Terhadap Penurunan Nyeri Fasciitis Plantaris Di Klinik Fisioterapi Siti Hajar - Nindia Putri; Bibit Wahyudi; Liza Agustin (Jurnal Kesehatan dan Fisioterapi, 2022)
Plantar fasciitis is a condition of lesions on the plantar fascia that causes pain, especially when the foot is first put on. Pain that arises will be felt starting from the sole of the foot to the heel of the foot. To overcome these problems, physiotherapy uses active stretching exercises for the plantar flexor ankle muscles to overcome the problems that arise. Objective : To determine the effect of active stretching of the ankle plantar flexor muscles on reducing plantar fasciitis pain at Klinik Fisioterapi Siti Hajar. Methods : This research is a quasi-experimental approach with a one-group design approach, which performs two VAS measurements before and after the exercise. Results : There was a significant decrease in the intensity of pain felt by the patient which was obtained through the p-value which showed a value of 0.001. Conclusion : There is an effect of active stretching of the ankleplantar flexor muscle on reducing plantar fasciitis pain at Klinik Fisioterapi Siti Hajar. Keywords: Plantar Flexor Ankle  And Fascitis Plantaris